The epistemology of resistance : gender and racial oppression, epistemic injustice, and resistant imaginations - d (New York : Oxford University Press, 2013)
This text explores the epistemic side of racial and sexual oppression. It elucidates how social insensitivities and imposed silences prevent members of different groups from listening to each other.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Resistance (Philosophy); Knowledge, Sociology of; Social epistemology; Epistemics; Oppression (Psychology)